Spectral characterization, microbial activities and toxicity study of some newly synthesized hydrazone derivatives - Kalaiarasi, N.; Manivarman, S. (International Journal of Advanced Chemistry, 2017)
Hydrazone derivatives of 2-Thioxodihyropyrimidine-2-dione were synthesized by addition of thiobarbituric acid with phenyl hydrazine, dinitrophenyl hydrazine, semicarbazide, thiosemicarbazide and benzohydrazide respectively. Structures of these synthesized compounds are characterized by means of UV, IR, Proton-NMR, Carbon- NMR. Finally the hydrazone derivatives synthesized are screened for biological activities namely antibacterial and antifungal activities. Also in addition the toxicity studies of the compounds are also performed.